Prostaglandin E2 induction of labor and cervical ripening for term isolated oligohydramnios in pregnant women with Bishop score ≤ 5. Issue 3 (March 2017) - Kansu‐Celik, Hatice; Gun‐Eryılmaz, Ozlem; Dogan, Nasuh Utku; Haktankaçmaz, Seval; Cinar, Mehmet; Yilmaz, Saynur Sarici; Gülerman, Cavidan
Abstract : Background : We aimed to evaluate the efficacy and safety of dinoprostone for cervical ripening and labor induction in patients with term oligohydramnios and Bishop score ≤ 5. Methods : This was a prospective case–control study, which included 104 consecutive women with a Bishop score ≤ 5. Participants were divided into two groups. Women with term isolated oligohydramnios and Bishop score ≤ 5 underwent induction of labor with a vaginal insert containing 10‐mg timed‐release dinoprostone (prostaglandin E2; Group A, n = 40). The control group, Group B, consisted of 64 cases of pregnancy with normal amniotic fluid volume (amniotic fluid index ≥ 5 cm) and Bishop score ≤ 5, and was matched for patient's age and parity. The primary outcome was time from induction to delivery; the secondary outcomes were the caesarean section (CS) rate, uterine hyperstimulation, rate of failed induction, and neonatal complications. Results : The mean time interval from induction to delivery was not different between the two groups ( p = 0.849), but there was a statistically significant difference between the groups in terms of the CS rate ( p = 0.005). There were no differences between the groups in neonatal outcome or perinatal morbidity or mortality. Conclusion : Dinoprostone appears to be a safe alternative for induction of labor in pregnancies with oligohydramnios. Induction of labor with dinoprostone in term pregnancies with isolated oligohydramnios is associated with increased rate of CS but there is no higher risk of perinatal complications.